Memory regulatory T cells home to the lung and control influenza A virus infection. Issue 9 (5th June 2019) - Lu, Chunni; Zanker, Damien; Lock, Peter; Jiang, Xiangrui; Deng, Jieru; Duan, Mubing; Liu, Chuanxin; Faou, Pierre; Hickey, Michael J; Chen, Weisan
Abstract: Memory regulatory T cells (mTregs) have been demonstrated to persist long‐term in hosts after the resolution of primary influenza A virus (IAV) infection. However, whether such IAV infection‐experienced (IAV‐experienced) mTregs differentiate into a phenotypically and functionally distinct Treg subset and what function they play at the infection site remains poorly defined. In this study, we characterized the phenotype, examined the responsiveness and assessed the suppressive function of IAV‐experienced memory Tregs (mTregs). In comparison with inexperienced naïve Tregs (nTregs), mTregs exhibited elevated expression of CD39, CD69, CD103, cytotoxic T lymphocyte‐associated antigen‐4, leukocyte function‐associated antigen‐1 and programmed cell death‐1 and could be activated in an antigen‐specific manner in vitro and in vivo . When mTregs and nTregs were adoptively cotransferred into recipient mice, mTregs had a competitive advantage in migrating to the IAV‐infected lungs. mTregs were more capable of controlling in vitro proliferation of CD4 + and CD8 + T cells and suppressed CD40 and CD86 upregulation on bone marrow‐derived dendritic cells. Adoptively transferred mTregs, but not adoptively transferred nTregs, significantly attenuated body weight loss, lung pathology and immune cell infiltration into the infected lungs after IAV infection. These results suggest that mTregs generated after IAV infection differentiate into a phenotypically distinct and functionally enhanced Treg subset that can be activated in an antigen‐specific manner to exert immunosuppression. We propose vaccination to induce such mTregs as a potential novel strategy to protect against severe IAV infection. Abstract : We show that memory regulatory T cells (mTregs) were more capable of controlling in vitro proliferation of CD4 + and CD8 + T cells and suppressed CD40 and CD86 upregulation on dendritic cells; and adoptively transferred mTregs, but not naïve Tregs, significantly attenuated body weight loss, lung pathology and immune cell infiltration into the influenza virus‐infected lungs.